HMGB-1 as a Novel Predictor of Disease Severity and Prognosis in Patients with Hemorrhagic Fever with Renal Syndrome - Hong Du; Jing Li; Haitao Yu; Jianqi Lian; Ye Zhang; Ying Zhang; Xuefan Bai; Pingzhong Wang (Mediators of Inflammation)
Objective. To examine the predictive capacity of the high mobility group box protein-1 (HMGB-1) for disease severity and prognosis of hemorrhagic fever with renal syndrome (HFRS). Methods. One hundred and five HFRS patients and 28 controls were studied. The concentrations of HMGB-1 in the blood were measured with a commercially available ELISA. The levels of white blood cells (WBC), platelets (PLT), hematocrit (HCT), albumin (ALB), blood urea nitrogen (BUN), serum creatinine (Scr), and uric acid (UA) were routinely tested in the same time frame. Results. The levels of HMGB-1 increased with the severity of the disease (P<0.001). HMGB-1 was positively correlated with WBC and BUN and negatively correlated with PLT, ALB, and UA (P<0.001). HMGB-1 showed statistical significance for predicting prognosis (AUC = 0.800, P<0.001). The sensitivity and specificity of HMGB-1, WBC, PLT, and ALB used in combination for predicting outcome were better than those of single analyses (AUC = 0.892, P<0.001). Conclusions. HMGB-1 can be considered a novel biomarker for severity and outcome in patients with HFRS. The use of HMGB-1, WBC, PLT, and ALB in combination to predict the outcome in patients with HFRS exhibited an acceptable level of diagnostic capability.